The Role and Importance of Cultural Intelligence and Its Components in a Multicultural Environment in the Opinion of Managers from Poland, Czechia and Italy - Agnieszka KNAP-STEFANIUK (Communications of International Proceedings, 2021)
Globalisation and a global scale of economic activity of an ever growing number of enterprises are inevitably linked with expanding mobility of both managers and employees. This mobility involves work in multinational companies and multicultural teams, whose members come from different countries and different cultures. Hence, the problems that stem from cultural differences are particularly relevant today, and the issue of cultural intelligence is highly topical. In a multicultural environment, managers’ cultural intelligence (Cultural Quotient-CQ) plays a crucial role in effective management of culturally diverse teams. CQ affects their openness in building positive intercultural relations in teams and their ability to understand and accept employees’ attitudes and behaviours, communication methods, working styles, and culture-dependent values. The concept of cultural intelligence includes four components: Metacognitive CQ, Cognitive CQ, Motivational CQ, and Behavioural CQ, all of which are vital in managing multicultural teams. The study described in the article (individual in-depth interviews conducted with the use of IT tools) is devoted to the analysis of the role and importance of cultural intelligence in a multicultural environment and was conducted among the Czech and Italian managers. The author describes the results of this study and also refers to her previous study (individual in-depth interviews) conducted among the Polish and Spanish managers. The main purpose of the article is to determine the role and importance of cultural intelligence in a multicultural environment from the perspective of managers participating in the interviews.
Keywords: Cultural Intelligence; Components of Cultural Intelligence; Cultural Diversity; Multicultural Environment; Managers